RELATIONSHIP OF NURSE SERVICE QUALITY WITH PATIENT SATISFACTION IN IN PATIENTROOMS GRANDMED HOSPITAL - Tati Murni Karokaro; Rawaty Sitorus; Peni Rio Ginting; Abdi Lestari Sitepu; Safril Matua Harahap (JURNAL KESMAS DAN GIZI (JKG), 2021)
Hospital is a health service that has permanent facilities and infrastructure consisting of professional medical personnel to provide health services, continuous nursing care, and diagnose and provide disease treatment to patients in need. The hospital must fulfill superior facilities, have professional human resources, all of which are part of influencing services to provide satisfaction to patients. This study aims to determine the relationship between the quality of nurse services and patient satisfaction in the inpatient room of the GrandMed Hospital, using a descriptive survey research type. The sample of this study was 27 patients in the Ns 4D room using a questionnaire instrument. The sampling technique used was purposive sampling. The results of the research obtained are those who have good quality nurse service 16 people (59.3%) and bad service quality 11 people (40.7%), 17 people who are satisfied (63.0%) and dissatisfied as many 10 people (37.0%), so that the results of the chi square statistical test obtained p value = 0.021, which means that there is a relationship between the quality of nurse services and satisfaction in the 4D patient room of Grandmed Hospital. From the results of this study, the advice that I can give is that nurse can apply the results of this research and make it into consideration for improving nursing services at the hospital not only in the 4D patient room but to all inpatient rooms at GrangMed Hospital. This research can be examined again with a larger number of samples and a larger number of rooms or hospitals in order to see more broadly about the effect of nursing services on patient satisfaction.